Training Job Interview Online Simulator for Hearing-Impaired People - Quintana, Nelba Graciela (2019)
This article describes an online training course for adult hearing-impaired individuals who use hearing aids or cochlear implants. This training course developed in HTML5 and JavaScript consists of a set of training activities to be solved online. The originality of this development is the recreation of a virtual scenario where a hearing-impaired person faces a job interview situation. This simulation strategy with multimedia features is based on a series of videos that recreate an office scenario where an interviewer asks questions that the interviewee must answer by choosing one of the options presented after every interviewer's question. The simulator prototype and the other activities make up a website developed in HTML5 and the PHP programming language. The user requires identification to have access to the site which has the ability to store in a MySQL relational base, the data of each registered person including the educational activities that he is carrying out each time he enters the training. The design of the proposal includes a pilot experience for the evaluation of the tool by a group of users by means of online surveys and personal interviews. According to the results, the optimization of the tool is foreseen for its subsequent implementation.